The impact of foreign ownership on return volatility, volume, and stock risks: Evidence from ASEAN countries - Naufa, Ahmad Maulin; Lantara, I. Wayan Nuka; Lau, Wee Yeap (Elsevier, 2019)
This paper aims to delve into the effect of foreign ownership on return volatility, volume, and risk of buying/holding stocks. It uses panel data from six ASEAN countries from 2007 to 2017. There are three primary findings. First, foreign ownership diminishes return volatility, particularly during and after a crisis. Second, it has a positive influence on the trading volume of a stock in the post-crisis, nonetheless negative during a crisis. Third, it reduces the asset and equity risks. However, these beneficial findings could be uniquely different in other ASEAN member economies. In conclusion, the benefits of foreign ownership outweigh the downside to it. © 2019